Assessment of readiness of Croatian companies to ontroduce I4.0 technologies - Rajka Hrbić; Tomislav Grebenar (Journal of Risk and Financial Management, 2022)
The main topic of this paper is to estimate the possibility and inclination of Croatian companies towards technology and innovation as well as to analyze advantages, limitations and risks involved with this significant technological leap. We analyzed 7147 Croatian business entities operating in different industries in this paper. The starting point in this research is to identify subjects, which could be users of I4.0 or its elements, based on the similarity of indicators with indicators of a sample of 58 identified I4.0 companies. We developed a machine-learning model by using the eXtreme Gradient Boosting algorithm (XGBoost) for this purpose, an approach that has not been used in any similar research. This research shows that the main difference between I4.0 and traditional industry is mostly observable in significantly better business performance of investment indicators, cost efficiency, technical equipment and market competitiveness. We identified 141 companies (1.97% of total analyzed sample) as potential users of I4.0, which makes up around 27% of total assets of the analyzed sample and around 26% of revenues.
Keywords: 650; Industry 4.0; artificial intelligence; machine learning; eXtreme Gradient Boosting (XGBoost); high-tech companies; impacts of I4.0 on business results; robotics